A Proposal for Folding in ORM Diagrams - Morgan, Tony (Springer Berlin Heidelberg, 2010)
Object Role Modeling (ORM) can be used to produce conceptual models of any scale. Although small examples are often used to illustrate specific points, it is equally possible to produce large models covering extensive business domains. To help users navigate around a large model, the ORM diagram is typically split over several virtual pages. This gives a fairly coarse granularity and it is difficult for users to change the page structure to meet some temporary viewing need. This paper describes an alternative approach that allows objects of lesser interest to be temporarily ’folded’ away and ’unfolded’ when required. The folding and unfolding can be dynamically controlled by the user, but operates under the control of specific algorithms. Some possible algorithms are discussed and illustrated with examples, and a number of usability issues are raised.